Color stability of Bos indicus bull steaks in modified atmosphere packaging (MAP) - Robertina dos Santos, Priscila (2016)
Evaluations of meat quality, including color, influence purchasing decisions and can be affected by type of fresh meat the packaging system. In this study, fresh steaks from Bos indicus bull were packaged in the vacuum (vacuum), 75% O2/25% CO2 (HiOx-MAP) and 40% CO2/0.4% CO/59.6% N2 (CO-MAP). Emphasis is placed on the color and lipid oxidation of bull beef steaks. Results reveal that the steaks stored in CO-MAP and HiOx-MAP exhibited similar or brighter red color than fresh steaks (exposed only to oxygen) or vacuum. The red color of the LD bull beef steaks packaged in CO-MAP was more intense than the color of meat stored in HiOx-MAP after the 14th day of storage. Vacuum packing dramatically impaired the color of the LD bull steaks, which were severely discolored (brown) after all storage times. Bos indicus steaks of all treatments showed extremely low TBARS values in all storage times. The results suggested that HiOx-MAP or CO-MAP may be utilized to stabilize or improve the red color of fresh steaks from bull of so appreciated by the consumer.